Information and consent - Hasinoff, Amy Adele (AoIR Selected Papers of Internet Research, 2013)
In 1999, a technology CEO stated: “You have zero privacy. Get over it.” Is it true that privacy is impossible online? By socializing on the internet and on mobile devices, users deliberately and inadvertently generate personal artifacts and data that can be persistent, easily replicable, and even searchable. While people have significant interests in protecting their private personal information, the existing rhetorical and legal tools to do so are limited. The solution proposed here is to adopt a standard that explicit consent should be necessary for the production, distribution, or possession of private media content and information. Given the quantity of personal information created and stored in digital formats, scholars, policymakers, technology developers, and users alike need to develop social norms and technological mechanisms for obtaining meaningful and informed consent before circulating private information.